Marijuana legalization and road safety: a panel study of US States - Young, Andrew R. (Kansas State University, 2019)
Policymakers and the public are concerned about the road safety implications of legalizing marijuana. Despite the more than two decades of data since California became the first state to legalize marijuana for medical use, there has been surprisingly little research on this question. This study seeks to address this gap in the literature. Specifically, this research combines twenty-three years of state traffic data with information on the contemporaneous legal status of marijuana, for both medical and recreational use, to estimate two models of road safety. First, while treating both the state and the year as fixed effects, the resulting panel regression model estimates that the legalization of medical or recreational marijuana is not a predictor of the number of fatalities per 100,000 vehicle-miles traveled. Second, due to limitations in the regression model, a difference-in-difference analysis was conducted over the same period and found no relationship between legalization of medical marijuana and the number of fatalities per 100,000 vehicle-miles traveled. These findings suggest that concerns of policy makers and the public that legalizing marijuana will worsen road safety are not ungrounded at this time. According to the models, the recent upward trend of traffic fatality rates nationwide is not a result of medical marijuana legalization. In fact, the legalization of marijuana is not found to be a predictor of traffic fatalities.
Keywords: Panel Study; Difference-in-Differences; Marijuana Legalization; Road Safety